Aggressive Angiomyxoma of the Vulva: A Précis for Primary Care Providers. (19th August 2013) - Elkattah, R.; Sarkodie, O.; Otteno, H.; Fletcher, A.
Abstract : Vulvar aggressive angiomyxoma (AA) is a rare mesenchymal tumor of the vulva. Due to its slow-growing nature, it is often overlooked and misdiagnosed by primary care providers (PCPs). We describe a case report of vulvar AA in a 38-year-old woman who underwent complete surgical excision of the neoplasm with no evidence of recurrence on a 5-year followup. A literature review follows to provide PCPs with the clinical, radiologic, and pathologic features that this tumor displays.